The Cellular Composition of the Innate and Adaptive Immune System Is Changed in Blood in Response to Long-Term Swimming Training - Morgado, José P.; Matias, Catarina N.; Reis, Joana Filipa; Curto, Dalia; Alves, Francisco Bessone; Monteiro, Cristina P. (Frontiers in Physiology, 2020)
Competitive swimming requires high training load cycles including consecutive sessions with little recovery in between which may contribute to the onset of fatigue and eventually illness. We aimed to investigate immune changes over a 7-month swimming season. Fifty-four national and international level swimmers (25 females, 29 males), ranging from 13 to 20 years of age, were evaluated at rest at: M1 (beginning of the season), M2 (after the 1st macrocycle’s main competition), M3 (highest training load phase of the 2nd macrocycle) and M4 (after the 2nd macrocycle’s main competition) and grouped according to sex, competitive age-groups, or pubertal Tanner stages. Hemogram and lymphocytes subsets were assessed by automatic cell counting and by flow cytometry, respectively. Self-reported Upper Respiratory Symptoms (URS) and training load were quantified. Although the values remained within the normal range reference, at M2, CD8+ decreased (M1 = 703±245 vs. M2 = 665±278 cell L-1; p=0.032) and total lymphocytes (TL, M1 = 2831±734 vs. M2 = 2417±714 cell L-1; p=0.007), CD3+ (M1 = 1974±581 vs. M2 = 1672±603 cell L-1; p=0.003), and CD4+ (M1 = 1102±353 vs. M2 = 929±329 cell L-1; p=0.002) decreased in youth. At M3, CD8+ remained below baseline (M3 = 622±245 cell L-1; p=0.008), eosinophils (M1 = 0.30±0.04 vs. M3 = 0.25±0.03 109 L-1; p=0.003) and CD16+56+ (M1 = 403±184 vs. M3 = 339±135 cell L-1; p=0.019) decreased, and TL, CD3+, and CD4+ recovered in youth. At M4, CD19+ were elevated (M1 = 403±170 vs. M4 = 473±151 cell L-1; p=0.022), CD16+56+ continued to decrease (M4 = 284±131 cell L-1; p<0.001), eosinophils remained below baseline (M4 = 0.29±0.05 109 L-1; p=0.002) and CD8+ recovered; monocytes were also decreased in male seniors (M1 = 0.77±0.22 vs. M4 = 0.57±0.16 109 L-1; p=0.031). The heaviest training load and higher frequency of URS episodes happened at M3. The swimming season induced a cumulative effect towards a decrease of the number of innate immune cells, while acquired immunity appeared to be more affected at the most intense period, recovering after tapering. Younger athletes were more susceptible at the beginning of the training season than older ones.